KESADARAN WAJIB PAJAK RESTORAN DALAM KEPATUHAN PELAPORAN PAJAK MENGGUNAKAN APLIKASI E-SPTPD DI KOTA DEPOK - Adinda Dwi Syahnaz (2021)
The purpose of this study was to determine the awareness of restaurant taxpayers in tax reporting compliance using the E-SPTPD application in Depok City. The method used in this research is a qualitative method with an interpretive paradigm and an ethnometodological approach. The sample of this study is restaurant owners who are registered and not yet registered as restaurant taxpayers in Depok City. The results of this study indicate that the lack of awareness of restaurant owners in restaurant tax reporting. This is due to the lack of knowledge of restaurant owners on taxation and the remote location makes it difficult for tax officers in the field to know the existence of the restaurant. The socialization carried out by the Depok City Regional Finance Agency has also not resulted in restaurant owners' awareness of their tax obligations because there are still many restaurant owners who are not present at the socialization.